Analisis Penerapan Target Costing sebagai Alat Pengendali Biaya Produksi Batubara dalam Meningkatkan Laba pada PT Kurnia Alam Investama - Raut Pisga Siregar (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2022)
This study was conducted to determine and analyze the calculation of target costing by applying the value engineering method, assessing the efficiency of production costs with target costing and anlyzing the application of target costing as a means of controlling coal production costs in increasing the profit of PT Kurnia Alam Investama. The sampling technique used in this study is criterion sampling with the following criteria: the research subject is PT Kurnia Alam Investama, has published financial reports for the last three years, and provides reports on production costs and coal sales reports for the last three years. Data and information obtained from interviews and company financial statement documents. The analytical technique used is qualitative method using three procedures including data condensation, data display and conclusions drowing/verifying. The results of the analysis show that: (1) the calculation of target costing by applying the value engineering method is proven to be able to reduce the cost of production, (2) the application of target costing is proven to create efficiency in production costs, and (3) the application of target costing as a means of controlling coal production costs is proven to increase profits.